(untitled) (Research, Society and Development, 2022)
Facing climate change is necessary to know the effects of temperature on plant development and identify which physiological factors are related to the reduction and/or increase in photosynthesis. This identification can be made in the first stages of development. Thus, the objective was to evaluate the physiological parameters of the sugarcane cultivar RB 86 7515 at 15°C, 28°C, and 40°C at different exposure times (0, 4, 8, 12, and 24 hours) and to evaluate 18S gene expression. The experiment was established in a completely randomized design, with six replications. Chlorophyll a and b were measured, and the a/b ratio, total chlorophyll in leaves, and variables related to photosystems. Initial (F0) and maximum (Fm) fluorescence values ​​were measured. The ratio Fv/Fo and the potential quantum efficiency of photosystem II (PSII) Fv/Fm were estimated. The mRNA was extracted using the same types of leaves used in the photosynthesis assessment. High temperatures with exposure for 24 hours affect the photosynthetic efficiency of sugarcane plants. Exposure of sugarcane plants with 65 days of development to 40 ºC for 24 hours is recommended to assess tolerance to temperature stress, aiming at early selection of genotypes.